Strengthening MSME Tax Compliance and Business Legality through Accounting and Tax Education in Bekasi Regency - Jamian Purba; Maulina Dyah Permatasari; Widiastuti Widiastuti; Salsabila Ameliani (Lentera Ilmu Nusantara, 2026)
This community service activity was motivated by the low level of accounting and taxation literacy among micro, small, and medium enterprise owners in Bekasi Regency, which affects financial management, tax compliance, and business legality. The purpose of the program was to improve participants' knowledge and skills in financial recordkeeping, understanding tax obligations, utilizing digital tax services, and increasing awareness of business legality. The program employed socialization, training, hands-on practice, and mentoring methods involving 13 business owners and was conducted at Pelita Bangsa University on May 29, 2026. Evaluation was carried out through observation, pre-tests, post-tests, and implementation assistance. The results indicated an improvement in participants' understanding of bookkeeping, preparation of simple financial statements, tax calculation and reporting, and business legalization procedures. Participants also demonstrated better ability to utilize digital tax services and implement more organized business administration practices. The activity confirms that structured education and mentoring can effectively enhance the managerial capacity of business owners in managing their enterprises professionally. Improved accounting and taxation literacy is expected to support higher tax compliance, strengthen business legality, and contribute to the sustainability and competitiveness of enterprises in the future.